Exploring cultural intelligence in educational studies: a bibliometric perspective on global literature - Laily Tiarani Soejanto; Khairul Bariyyah; Santy Andrianie; Setyorini Setyorini; Restu Dwi Ariyanto; Abu Yazid Abu Bakar (COUNS-EDU: The International Journal of Counseling and Education)
With the rapid growth of research on the topic of cultural intelligence in educational studies, it becomes increasingly important to understand the trends, patterns of scholarly collaboration, and direction of this research development. This study explores the development of research on the topic based on Scopus-indexed scientific publications, using a bibliometric approach. Data were obtained from 227 relevant articles based on the keywords “cultural intelligence” and “education” from 2015 to 2025. The analysis was conducted using VOSviewer and Biblioshiny to answer research questions. RQ1: Who are the authors who contribute the most to the publication of research and works on cultural intelligence in education studies? RQ2: What are the main keywords in cultural intelligence in education studies? RQ3: What are the potential topics for future studies in the field of research related to cultural intelligence in educational studies? Based on these research questions, it was found that Jacqueline E. McLaugh is the most prolific author. In addition, four main clusters of research were found, namely the Education and Students Cluster, the Cultural and Psychological Competence Cluster, the Learning and Cognition Cluster, and the Globalization, Leadership, and Cultural Diversity Cluster. Potential research on the topic of cultural intelligence in educational studies focuses on how cultural intelligence can increase international employment and how students can develop better skills in multicultural experiential learning.